Clozapine generates obsessive compulsive disorder-like behavior in mice - Shinwon Kang; Hyun Jong Noh; Soo Hyeon Bae; Yong-Seok Kim; Hogun Lew; Jisoo Lim; Se Joo Kim; Kyung Sue Hong; Jong-Cheol Rah; Chul Hoon Kim (Molecular Brain, 2020)
Abstract Clozapine is thought to induce obsessive compulsive symptoms (OCS) in schizophrenic patients. However, because OCS are often comorbid with schizophrenia regardless of clozapine treatment, it remains unclear whether clozapine can generate OCS de novo. Thus, it has been difficult to establish a causal link between clozapine and OCS in human studies. To address this question, we asked whether chronic treatment with clozapine can induce obsessive compulsive disorder (OCD)-like behavior in mice. We injected mice with long-term continuous release pellets embedded with clozapine four times at 60-day intervals and then monitored the mice for signs of OCD-like behavior up to 40 wk. of age. We found clozapine increases grooming behavior as early as 30 wk. of age. We also investigated the effect clozapine on grooming behavior in Sapap3 knockout (KO) mice, which are a well-known animal model of OCD. In Sapap3 heterozygous KO mice, clozapine increases grooming behavior much earlier than in wild-type mice, suggesting a clozapine-OCD gene interaction. Fluoxetine, which is often used in the treatment of OCS and OCD, reduced the grooming behavior induced by clozapine. These data demonstrate that chronic clozapine treatment can generate OCD-like behavior in mice and support the hypothesis that clozapine produces de novo OCS regardless of schizophrenia status.